New Salicylanilide Derivatives and Their Peptide Conjugates as Anticancer Compounds: Synthesis, Characterization, and In Vitro Effect on Glioblastoma - Horváth, Lilla; Biri-Kovács, Beáta; Baranyai, Zsuzsa; Stipsicz, Bence; Méhes, Előd; Jezsó, Bálint; Krátký, Martin; Vinšová, Jarmila; Bősze, Szilvia (ACS omega, 2024)
Pharmacologically active salicylanilides (2-hydroxy-N-phenylbenzamides) have been a promising area of interest in medicinal chemistry-related research for quite some time. This group of compounds has shown a wide spectrum of biological activities, including but not limited to anticancer effects. In this study, substituted salicylanilides were chosen to evaluate the in vitro activity on U87 human glioblastoma (GBM) cells. The parent salicylanilide, salicylanilide 5-chloropyrazinoates, a 4-aminosalicylic acid derivative, and the new salicylanilide 4-formylbenzoates were chemically and in vitro characterized. To enhance the internalization of the compounds, they were conjugated to delivery peptides with the formation of oxime bonds. Oligotuftsins ([TKPKG]n, n = 1-4), the ligands of neuropilin receptors, were used as GBM-targeting carrier peptides. The in vitro cellular uptake, intracellular localization, and penetration ability on tissue-mimicking models of the fluorescent peptide derivatives were determined. The compounds and their peptide conjugates significantly decreased the viability of U87 glioma cells. Salicylanilide compound-induced GBM cell death was associated with activation of autophagy, as characterized by immunodetection of autophagy-related processing of light chain 3 protein.